2019
DOI: 10.4103/jcas.jcas_171_18
|View full text |Cite
|
Sign up to set email alerts
|

Fractional carbon dioxide laser: Optimizing treatment outcomes for pigmented atrophic acne scars in skin of color

Abstract: Dark skin type has high propensity to acne scarring and is often complicated by persistent erythema or pigmentation at the base. Fractional lasers are available for the longest period and are able to improve most atrophic acne scars. Often pigmented scar bases and dark skin types limit the use of aggressive laser parameters. Long pulse mode is preferred over short pulse to prevent epidermal damage; low fluence is chosen versus high fluence and low density versus high density. Repeated treatments are needed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 41 publications
(57 reference statements)
0
25
0
3
Order By: Relevance
“…Thermal injury generates coagulation and denaturation of collagen and re-epithelialization ensues. 5 Fractional CO 2 laser resurfacing has been successfully used in the treatment of atrophic acne scars and for skin rejuvenation. There are also some reports of its usefulness in hypertrophic as well as burn scars 6. Very few studies assessed fractional CO 2 laser in treatment of post-traumatic linear scars besides they were studied as part of different types of atrophic scarring.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal injury generates coagulation and denaturation of collagen and re-epithelialization ensues. 5 Fractional CO 2 laser resurfacing has been successfully used in the treatment of atrophic acne scars and for skin rejuvenation. There are also some reports of its usefulness in hypertrophic as well as burn scars 6. Very few studies assessed fractional CO 2 laser in treatment of post-traumatic linear scars besides they were studied as part of different types of atrophic scarring.…”
Section: Introductionmentioning
confidence: 99%
“…MTZs formed are variable according to the fluence used and the depth of penetration achieved. Thermal injury generates coagulation and denaturation of collagen and re‐epithelialization ensues 5 . Fractional CO 2 laser resurfacing has been successfully used in the treatment of atrophic acne scars and for skin rejuvenation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tissue cells outside the heat loss area are not damaged and can be quickly repaired by cell migration. [ 12 13 ] So as to achieve the purpose of skin tightening, removing aging skin, and removing skin pigment spots. Generally speaking, the epithelium of the area treated by the lattice laser can be completely recovered within 24 hours, so that the risk of skin infection is low, and the erythema period of the skin is also shortened.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a lack of studies using these modalities for the prevention of scarring prior to injury, however, in vitro studies have demonstrated transdermal patches have the potential to inhibit hypertrophic scar formation [ 7 , 8 , 9 ]. Some recent studies support the concept of priming the skin prior to an invasive intervention for achieving an optimal result [ 10 , 11 , 12 , 13 , 14 , 15 ]. However, the concept of pre-emptively priming the skin prior to surgically induced injury has not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 99%